Legal Protection against Bouwheer in a Contract for the Outsourcing of Work with a Bank Guarantee - Permatasari, Made Intan; Budiartha, I Nyoman Putu; Jaya Utama, I Wayan Kartika (Journal of Law, Politic and Humanities, 2025)
Bank guarantee is a guarantee in a work outsourcing agreement that protects the bouwheer from the contractor's default. However, in practice, the disbursement of bank guarantees often faces obstacles, especially when the contractor goes bankrupt. Banks often refuse disbursements for administrative reasons that do not have a clear legal basis, thus creating legal uncertainty for bouwheer. This research uses normative legal methods with legislative, conceptual and case approaches. This approach is used because there are vague norms in the arrangement of bank guarantees, especially regarding legal protection for bouwheer. Although there are regulations on bank guarantees, the existing rules focus more on the responsibility of banks without explicitly regulating bouwheer's rights in the disbursement of collateral. The results of the study show that legal protection for bouwheer is divided into preventive and repressive protection. Preventive protection includes strict contractual clauses, the selection of credible banks, and supervision of the execution of guarantees. Repressive protection is carried out through non-litigation and litigation channels in the event of disbursement denial without a valid reason. Decision No. 159/Pdt.G/2023/PN Ptk emphasizes that banks are still obliged to disburse guarantees even if the contractor is bankrupt, and rejection without legal basis can be categorized as default by banks.